Tailoring Adaptive Social Safety Nets to Latin America and the Caribbean - Williams, Asha (World Bank E-Library Archive, 2020)
Given this, there is unlocked potential in LAC to effectively respond to disasters by systematically using SSNs when appropriate. This note presents key lessons and design considerations for LAC countries to better usetheir SSNs to help individuals and households prepare, cope and adapt to the shocks they face. While this note focuses on disasters caused by natural hazards, the framework and lessons presented here are applicable to other types of emergencies and shocks